Association of functional MMP-2 gene variant with intracranial aneurysms: case-control genetic association study and meta-analysis. (4th May 2018) - Alg, Varinder S.; Ke, Xiayi; Grieve, Joan; Bonner, Stephen; Walsh, Daniel C.; Bulters, Diederik; Kitchen, Neil; Houlden, Henry; Werring, David J.; ,
Abstract: Introduction: Abnormalities in Matrix Metalloproteinase (MMP) genes, which are important in extracellular matrix (ECM) maintenance and therefore arterial wall integrity are a plausible underlying mechanism of intracranial aneurysm (IA) formation, growth and subsequent rupture. We investigated whether the rs243865 C > T SNP (single nucleotide polymorphism) within the MMP-2 gene (which influences gene transcription) is associated with IA compared to matched controls. Materials and Methods: We conducted a case-control genetic association study, adjusted for known IA risk factors (smoking and hypertension), in a UK Caucasian population of 1409 patients with intracranial aneurysms (IA), and 1290 matched controls, to determine the association of the rs243865 C > T functional MMP-2 gene SNP with IA (overall, and classified as ruptured and unruptured). We also undertook a meta-analysis of two previous studies examining this SNP. Results: The rs243865 T allele was associated with IA presence in univariate (OR 1.18 [95% CI 1.04–1.33], p  = .01) and in multi-variable analyses adjusted for smoking and hypertension status (OR 1.16 [95% CI 1.01-1.35], p  = .042). Subgroup analysis demonstrated an association of the rs243865 SNP with ruptured IA (OR 1.18 [95% CI 1.03–1.34] p  = .017), but, not unruptured IA (OR 1.17 [95% CI 0.97–1.42], p  = .11). Conclusions: Our study demonstrated an association between the functional MMP-2 rs243865 variant and IAs. Our findings suggest a genetic role for altered extracellular matrix integrity in the pathogenesis of IA development and rupture.